204 Idiopathic intracranial hypertension in Wales: population characterisation, epidemiological trends and healthcare utilisation. Issue 6 (27th May 2022) - Miah, Latif; Strafford, Huw; Fonferko-Shadrach, Beata; Hollinghurst, Joe; Rees, Mark I; Sawhney, Inder; Hadjikoutis, Savvas; Powell, Rob; Lacey, Arron; Owen Pickrell, W
Abstract : Objective: To characterise the Welsh idiopathic intracranial hypertension (IIH) population, epidemiologi- cal trends and healthcare outcomes using routinely collected healthcare data. Methods: We used primary and secondary care healthcare diagnostic codes within the Secure Anonymised Information Linkage databank to ascertain IIH cases and controls in a retrospective cohort study between 2003–2017. We validated IIH diagnosis codes using anonymised secondary care lists of IIH cases. Results: We analysed 35 million patient years of data (2003–2017). There were 1765 cases of IIH in 2017 (85% female). The prevalence and incidence of IIH in 2017 was 76/100, 000 and 7.8/100, 000, significantly increased from 2003 (prevalence=12/100, 000, incidence=2.3/100, 000). IIH prevalence is associated with socio-economic deprivation and increasing body mass index (BMI). 9% of people with IIH had CSF shunts with less than 0.2% having bariatric surgery. Unscheduled hospital admissions were significantly higher in the IIH cohort compared to controls; and also in IIH patients with CSF shunts compared to those without. Conclusions: IIH incidence and prevalence is increasing significantly, corresponding to population increases in BMI. This has important implications for healthcare professionals and policy makers given the comor- bidities, complications and increased healthcare utilisation and economic burden associated with IIH. lotif_miah@hotmail.com